Developing academic talent as a practicing school psychologist: From potential to expertise. Issue 10 (16th March 2020) - Dixson, Dante D.; Olszewski‐Kubilius, Paula; Subotnik, Rena F.; Worrell, Frank C.
Abstract: In this article, we explore how school psychologists who adopt a talent development perspective can play a larger role in cultivating the talent of academically gifted students. Utilizing the talent development megamodel and Ackerman's model of expertise, we outline how school psychologists can consult with school administrators, teachers, and parents to meet the general and domain‐specific academic needs of academically gifted students at home and in school. In addition, we discuss how school psychologists can leverage systems of assessment (e.g., universal screening, continued assessment) to identify academically gifted students across academic talent trajectories as well as provide students with multiple opportunities to exhibit their academic talents. We conclude by highlighting some diversity and multi‐cultural considerations that school psychologists should keep in mind while developing academic talent, as well as a policy implication of school psychologists adopting a talent development approach to their work.